Deformation approach to the calculation of compressive strength of steel-reinforced concrete elements - D. N. Lazouski; A. I. Hil; D. O. Hlukhau (Vestnik MGSU)
Introduction. Compressed steel-reinforced concrete structures, due to the requirements of reduced cross-sectional dimensions for vertical load-bearing structures with high strength and rigidity of structures, as well as their fire resistance, are widely used throughout the world in the construction of high-rise buildings, entertainment structures, etc. Methods for their calculation are constantly being improved. The deformation approach to calculation makes it possible to obtain the parameters of their stress-strain state (SSS) at any stage of deformation under load, to take into account physical nonlinearity of the materials and the loading stages.Materials and methods. The selection of compressed steel-reinforced concrete elements for the theoretical study was made according to the data published in open sources. A cross-sectional model was compiled, taking into account the joint work of concrete, rigid and flexible reinforcement, and their deformation diagrams, taking into account physical nonlinearity. A criterion for the destruction of the cross section of a steel-reinforced concrete element without limiting the limiting deformations of materials under compression is proposed.Results. The prerequisites for using the deformation approach to the calculation of steel-reinforced concrete elements are formulated. Two stages of their operation are considered: under the action of forced shrinkage deformations during concrete hardening and subsequent loading. Using examples of the accepted specimen of compressed steel-reinforced concrete elements, the advantages of the deformation approach in their calculation are shown.Conclusions. The deformation approach to calculation makes it possible to obtain the SSS parameters of compressed steel-reinforced concrete elements of arbitrary cross-section shape with different distribution of reinforcement over the cross-section, to take into account the nonlinearity of deformation of materials, concrete shrinkage. The proposed criterion for the destruction of compressed steel-reinforced concrete elements allows to take into account the redistribution of forces between concrete, rigid and flexible reinforcement to full extent.